Acute medial clavicle fracture in adults: a systematic review of demographics, clinical features and treatment outcomes in 220 patients - Saeed Asadollahi; Andrew Bucknill (Journal of Orthopaedics and Traumatology, 2019)
Abstract Background Medial third clavicle fractures are rare injuries, with limited information available on their characteristics or treatment results. Materials and methods We performed a systematic review according to PRISMA guidelines to evaluate the demographics, clinical profile, management and treatment outcome. Electronic searches of the MEDLINE, EMBASE and Cochrane databases were performed. Results Seventeen studies were included, consisting of 7 case series and 10 case reports. Two hundred twenty fractures were identified. Seventy-eight percent of fractures occurred in men with mean age of 48 years (16–94 years). Road traffic accident was the most common mechanism of injury (64%). Associated injuries occurred in 81% of patients, with thoracic trauma being the most common (47%). The most common fracture type was extra-articular, with no or minimal displacement (60%). In 9% of patients the fracture was segmental. One hundred ninety-one patients received nonoperative treatment. Twenty-nine patients were treated operatively. The overall nonunion rate was 5% (7/137). The nonunion rate following nonoperative management was 4.6% (5/108). The functional result following nonoperative treatment indicated overall “good” functional outcome. There was no report of catastrophic intraoperative complication amongst patients undergoing surgical fixation. Conclusion Medial third clavicle fractures represent a distinct subgroup of clavicle fractures. Nonoperative treatment of these fracture seems to result in high union rate and overall favourable functional outcome. Further high-quality research in this area is warranted to investigate the outcomes and indication for nonoperative versus operative management of these fractures. Level of evidence IV.